2007
DOI: 10.4489/myco.2007.35.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Keratinase from a Feather-Degrading Fungus,Aspergillus flavusStrain K-03

Abstract: A keratinolytic enzyme secreted by Aspergillus flavus K-03 cultured in feather meal basal medium (FMBM) containing 2% (w/v) chicken feather was purified and characterized. Keratinolytic enzyme secretion was the maximal at day 16 of the incubation period at pH 8 and 28℃. No relationship was detected between enzyme yield and increase of fungal biomass. The fraction obtained at 80% ammonium sulfate saturation showed 2.39-fold purification and was further purified by gel filtration in Sephadex G-100 followed by io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 42 publications
(38 reference statements)
2
30
1
Order By: Relevance
“…The major livestock's of keratin includes goatskins, sheepskins, cattle hides and buffalo hides as shown in Fig 1. Skin and its appendages such as nails, hair, feathers, wool, hooves, scales and stratum corneum are the richest source of keratin (Kim 2007). It can be extracted from animal horns and hooves wool and human hairs (Fig.…”
Section: Sources Of Keratin Biomassmentioning
confidence: 99%
“…The major livestock's of keratin includes goatskins, sheepskins, cattle hides and buffalo hides as shown in Fig 1. Skin and its appendages such as nails, hair, feathers, wool, hooves, scales and stratum corneum are the richest source of keratin (Kim 2007). It can be extracted from animal horns and hooves wool and human hairs (Fig.…”
Section: Sources Of Keratin Biomassmentioning
confidence: 99%
“…Another research done by Malathi and Chakraborty (1991), reported the new alkaline protease produced by A. flavus useful in tannery industry. Kim (2007), revealed the ability of A. flavus in production of keratinase that is used in enzymic catalysis of keratin from feather. Moreover, Chellapandi (2010), revealed the production of tannery protease by A. flavus and A. terreus.…”
Section: Application In Leather Industrymentioning
confidence: 99%
“…Keratin is a major component of feathers [1] It is an insoluble structural protein in epithelial cells of vertebrates [2]. Keratin is also very rich in amino acids like Leucine and Serine [3].…”
Section: Introductionmentioning
confidence: 99%